We could be beautiful : a novel - Huntley, Swan (Doubleday, 2016)
Feeling empty in spite of the wealth that affords her a luxurious Manhattan apartment, designer accessories, and fine art, Catherine West pursues a relationship with the son of a family friend who her Alzheimer's patient mother only remembers negatively.